The Effect of Using Learning Modules on Student Learning Outcomes - Muslim, Fachruddiansyah; Mayasari; Refnida; Putra, Iwan (Indonesian Scientific Publication, 2024)
The purpose of this study is to find out the effect of epub-based learning modules on the learning outcomes of students in macroeconomics courses of the teacher training of Jambi University and faculty of education, economic education. This type of study is parallel convergent mixing. The sample of this study is 105 students of the Faculty of Teacher Education and Education, University of Jambi. Questionnaires and multiple-choice questions were used as working tools. The results showed that the use of epub-based modules affected the academic performance of the 2020/2021 students of Jambi University Teacher Training and Faculty of Education in macroeconomic subjects.